한의사의 의료영상장비 사용에 대한 방사선사의 인식도 - 최재호(JaeHo Choi); 강기봉(GiBong Kang); 김상현(SangHyun Kim); 김태희(TaeHee Kim); 김규형(GyooHyung Kim); 이미화(MiHwa Lee); 안중성(JungSeong Ahn); 홍성완(SeongWan Hong); 이재석(JaeSeok Lee); 권익수(IckSu Kwon10); 박재윤(JaeYoon Park) (방사선기술과학, 2017)
In order to examine how Radiological Technologists perceive the oriental doctor's use of Medical Imaging Equipment, surveys were conducted for the members of the Korean Radiological Technologists Association. The total number of respondents were 515 and 481, with 34 insincere responses removed caused of nonvalidated answer. The results of the analysis are as follows. Although there were no statistical significance in the difference in perception by location of residence, work place, and educational background, respondents with higher education showed a tendency to agree on the use of comprehensive medical imaging equipment, but tended to oppose the use of special medical imaging equipment. Differences in perception by gender showed a greater negative perception toward the oriental doctor's use of medical imaging equipment by women than men. In particular, women showed more negative tendency for oriental doctor's use of special medical imaging equipment such as MRI, CT, and ultrasound equipment compared to men, and this was statistically significant. The difference in perception by age showed that the oriental doctor's use of medical imaging equipment was negative in the 20~30s, neutral in the 40~50s, and positive in the 60s, which were statistically significant. The difference in perception by work experience showed that the longer the work experience was, the more positive it was toward oriental doctor's use of medical imaging equipment. Specifically, the most favorable tendency was found with work experience of more than 30 years, which was statistically significant. The results of this study revealed the Radiological Technologists' perceptions on the oriental doctor's use of Medical Imaging Equipment and this can contribute to the direction of public health promotion in the future. 한의사 의료영상장비 사용에 대하여 방사선사의 인식도를 알아보고자 대한방사선사협회 영상의학기술학회의 회원을 대상으로 자체적으로 개발한 설문지를 통하여 설문조사를 하였으며 총 응답 515명, 부적격 응답 34명을 제외한 481명의 설문을 바탕으로 연구하였으며 분석한 결과는 다음과 같다. 거주지, 근무기관, 학력에 따른 인식도 차이에서 통계적 유의성을 보이지 않았으나 고학력일수록 포괄적인 의료영상장비의 사용에는 동의하는 경향이 있었다. 그러나 특수의료영상장비의 사용에는 반대하는 경향이 보였다. 성별에 따른 인식도 차이에서는 남성보다 여성에서 한의사 의료영상장비 사용에 대하여 부정적 인식이 큰 것으로 나타났다. 특히 MRI나 CT, 초음파와 같은 특수의료영상장비를 이용하는 것에 대하여 남성보다 부정적인 경향이 나타났으며 이는 통계적으로 유의하였다. 연령에 따른 인식도 차이에서는 한의사의 의료영상장비 사용에 대하여 20~30대는 부정적, 40~50대는 중립적, 60대에서 긍정적으로 나타났으며 모든 문항에서 통계적으로 유의하였다. 근무경력에 따른 인식도 차이에서는 한의사의 의료기기 사용에 근무경력이 오래될수록 긍정적으로 나타났다. 특히 30년 이상의 근무경력에서 가장 긍정적 경향이 나타났으며 이는 통계적으로 유의하였다. 이번 연구를 통해 방사선사의 한의사 의료영상장비 사용의 인식을 알 수 있었으며, 이러한 연구 결과들은 앞으로의 국민 건강증진을 위한 방향성 제시에 기여할 것으로 생각된다.